What are the functions of discourse markers uh & um? - Darius Yonatan Nama (Prominent, 2021)
Abstract: This paper examines the function of uh and um in spontaneous speaking by an English native speaker which focuses on the analysis of the function of delay markers in conversation particularly in answering questions spontaneously. The data was collected from an interview with an English native speaker as the participant, a male Australian postgraduate student of an Australian university. The utterances in the transcript were analyzed applying the conversation analysis method. It is found that there are some functions of uh and um in the participant’s speech such as; looking for the answer by repeating the question, searching for words, changing the structure of the sentence after pausing, keeping the floor, deciding what to say next, pausing in his long answer and pausing in his first utterance, repeating the question before answering it and ceding the floor.